Identification of the novel allele, HLA‐DRB1*08:03:12, in a Chinese cord blood donor. (24th February 2022) - Fu, Rui; Wang, Fang; Zhao, Shuoxian; Zhang, Wei; Zhu, Faming
Abstract : HLA‐DRB1*08:03:12 differs from HLA‐DRB1*08:03:02 by a single nucleotide substitution at position 702C>T.